Do the Leaves of Multiple Invasive Plants Decompose More Easily than a Native Plant’s under Nitrogen Deposition with Different Forms? - Chuang Li; Yue Li; Shanshan Zhong; Zhelun Xu; Zhongyi Xu; Mawei Zhu; Yuqing Wei; Congyan Wang; Daolin Du (Nitrogen, 2024)
This study aimed to clarify the differences in the decomposition rates, soil carbon and nitrogen contents, soil enzyme activities, and the structure of the soil bacterial community between the four Asteraceae invasive plants (AIPs), Bidens pilosa L., Conyza canadensis (L.) Cronq., Solidago canadensis L., and Symphyotrichum subulatum (Michx.) G.L. Nesom, and the native plant Pterocypsela laciniata (Houtt.) Shih under the artificially modeled nitrogen with four forms (including nitrate, ammonium, urea, and the mixed nitrogen forms with an equal mixture of three individual nitrogen forms). The mixed nitrogen forms significantly increased the decomposition rate of the four AIPs and P. laciniata. The positive effects of the mixed nitrogen forms on the decomposition rate of the four AIPs and P. laciniata were obviously greater than those of individual nitrogen forms. Nitrogen with four forms visibly up- or down-regulated the dominant role of predominant soil bacterial biomarkers, and significantly increased the species number, richness, and phylogenetic diversity of the soil bacterial community, as well as the number of most of the functional gene pathways of the soil bacterial communities involved in the decomposition process. The decomposition rate of the four AIPs was similar to that of P. laciniata. The leaves of C. canadensis decomposed more easily than those of S. subulatum. The decomposition process of the four AIPs caused remarkable changes in the relative abundance of several taxa of the soil bacterial community and soil bacterial beta diversity, and caused apparent up- or down-regulation in the dominant role of predominant soil bacterial biomarkers and the number of several functional gene pathways of the soil bacterial communities involved in the decomposition process.